Endoscopic treatment of symptomatic fibroids at reproductive age and beyond. Issue 6 (2nd November 2017) - Abdusattarova, Khulkar; Mettler, Liselotte; Alkatout, Ibrahim; Dempfle, Astrid
Abstract: Objectives: To evaluate the feasibility of endoscopic treatment of symptomatic uterine fibroids based on patient and fibroid characteristics in reproductive, pre-menopausal and post-menopausal women. Material and methods: The medical records of women with symptomatic uterine fibroids who underwent surgical procedures from 2010 to 2015 were retrospectively reviewed. Results: A total of 819 patients, of which 710 (86.6%) underwent endoscopic procedures. The mean age of women who underwent laparoscopic myomectomy (LM) was 36.77 ± 6.54 and hysteroscopic myomectomy (HSCM) was 43.10 ± 10.26. The mean cumulative diameter of fibroids in the LM was 8.94 ± 3.1 and 3.68 ± 1.64 cm in the HSCM. Furthermore, LM and HCSM were performed when the mean diameter of the largest fibroid was up to 18.50 and 5.5 cm, respectively. The mean age of women in laparoscopic supracervical hysterectomy (LSH) was 46.02 ± 6.13 and total laparoscopic hysterectomy (TLH) was 47.30 ± 8.12. The mean cumulative diameter of fibroids in the LSH was greater than in the TLH, at 8.94 ± 3.1 and 7.63 ± 3.60 cm, respectively. Conclusions: Uterus-preserving procedures are feasible, even if the largest fibroid diameter is more than 10 cm in LM and equal to 5.5 cm in HSCM. For pre- and post-menopausal women, TLH is the definitive treatment modality for uterine fibroids, and LSH represents an alternative to TLH.